A hybrid deconvolution approach to separate static and moving single-tone acoustic sources by phased microphone array measurements. (1st February 2017) - Mo, Pinxi; Jiang, Weikang
Abstract: Beamforming approaches are developed to locate and quantify either static or moving acoustic sources by phased microphone array measurements. They would meet difficulties in mapping combined sources consisting of both static and moving sources. In this work, a hybrid deconvolution approach is proposed to separate static and moving single-tone sources. The approach is derived based on the source independence assumption as in the Deconvolution Approach for the Mapping of Acoustic Sources (DAMAS). The static beamforming and the moving beamforming are integrated to construct a linear matrix equation. The source distributions for the static sources and moving sources are simultaneously obtained by solving the equation. Numerical simulations and experiments were implemented on the combined sources with one static source and one rotating source. From the results, the hybrid deconvolution approach shows its effectiveness in separating the two sources, even with large source strength differences. Highlights: The PSF matrixes Asm, Ams and Amm are firstly proposed in analogy to DAMAS. The approach is proposed by integrating the static beamforming and moving beamforming. One static source and one rotating source are identified in simulations and experiments.